Obesity pharmacotherapy: options and uses in clinical practice - Kahan, Scott (Henry Stewart Talks, 2017)
Introduction to obesity pharmacotherapy, Phentermine, Orlistat, Lorcaserin, Phentermine/Topiramate ER, Bupropion SR/Naltrexone SR, Liraglutide, Long term effects of therapy, Choosing between drug options, Future directions of obesity pharmacotherapy